Jejunal Metabolic Responses to Escherichia coli Infection in Piglets - Wu, Hucong; Liu, Jiaqi; Chen, Siyuan; Zhao, Yuanyuan; Zeng, Sijing; Bin, Peng; Zhang, Dong; Tang, Zhiyi; Zhu, Guoqiang (Frontiers in Microbiology, 2018)
This study aimed to investigate the jejunal metabolic variations in enterotoxigenic Escherichia coli (ETEC)-infected piglets. Piglets were infected with 1×1010 CFUs (colony-forming units) of ETEC W25K and assigned into diarrheal, recovered, control, and resistant groups. Jejunal samples were harvested at day 6 and metabolic profiles were analyzed via gas chromatography coupled to time-of-flight mass spectrometry (GC/TOFMS). The results showed that 33 metabolites in the jejunum were identified in ETEC-induced diarrhea, including amino acids, fatty acids, sugars, and organic acids. Compared with the control, resistant, and recovered piglets, diarrheal piglets showed higher concentrations of 4-aminobutyric acid (GABA) and glycine in the jejunum. Compared with the control and resistant piglets, six metabolites were markedly decreased in diarrheal piglets, including ornithine, asparagine, glutamine, citric acid, citrulline, and lysine. Collectively, this study provides insights into jejunal metabolic response to ETEC infection and ETEC induced diarrhea in piglets.